Electronic States and Light Absorption in a Cylindrical Quantum Dot Having Thin Falciform Cross Section - Dvoyan Karen; Hayrapetyan David; Kazaryan Eduard; Tshantshapanyan Ani (Nanoscale Research Letters, 2008)
Abstract Energy level structure and direct light absorption in a cylindrical quantum dot (CQD), having thin falciform cross section, are studied within the framework of the adiabatic approximation. An analytical expression for the energy spectrum of the particle is obtained. For the one-dimensional “fast” subsystem, an oscillatory dependence of the wave function amplitude on the cross section parameters is revealed. For treatment of the “slow” subsystem, parabolic and modified Pöschl-Teller effective potentials are used. It is shown that the low-energy levels of the spectrum are equidistant. In the strong quantization regime, the absorption coefficient and edge frequencies are calculated. Selection rules for the corresponding quantum transitions are obtained.